(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
An Internet of Things (IoT) enables devices to gather and share data directly with one another and along with clouds, enabling for faster and more effective data collecting, recording, as well as analysis. This opens up a world of possibilities in a range of industries, including such autonomous cars that recognize wear and tear as well as schedule repairs, or trains that dynamically calculate and broadcast anticipated arrival times to waiting passengers. Nowhere is the Internet of Things more promising than in health, in which its concepts are already being applied to improve access to treatment, improve quality, as well as, most importantly, reduce costs. The use of different technologies, such as information technology (IT), to complement and improve current healthcare services has been the subject of much study. The Internet of Things (IoT) has indeed been widely utilized to connect current medical resources as well as provide reliable, effective, and intelligent treatment to the aged and chronically ill. Recognizing the benefits and drawbacks of any innovation is critical to its successful implementation. This article presents a descriptive assessment of the Smart Healthcare Platform’s benefits and drawbacks. The smart healthcare platform’s history is also discussed.